Customer mistreatment and employees' emotional exhaustion: moderating role of gender/ Nur Hidayah Jesni and Mohd Onn Rashdi Abd Patah - Jesni, Nur Hidayah; Abd Patah, Mohd Onn Rashdi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Employees of quick service restaurant often have to face mistreatments from customers because of different reasons and situations. Customer mistreatment affects employees emotionally and consequently took a toll on their motivation, and other work-related problems. The purpose of this research is to examine the cause of customer mistreatment and its effect on frontline fast food employees' emotional state. Data was collected from 121 quick service restaurant employees in Kuala Lumpur and Selangor, Malaysia. The data obtained through self-administered questionnaires were then analyzed using SPSS statistical tool. The finding of the study brings new discovery on the issue of customer mistreatment on employee's emotional exhaustion in quick service restaurants in Malaysia. Therefore, this study aims to improve the awareness about employees' emotional state and future research might explore the other work-related factors to emotional exhaustion of restaurant employees especially in the local setting.